Student’s Entrepreneurship Interest in Terms of Contextual and Personal Factor - Tegowati Tegowati; Dian Palupi; Widhi Ariestianti Rochdianingrum (School of Business, IPB University (SB-IPB), 2019)
This study aims to review the interests of student entrepreneurship from contextual factors and personal factors. The population in this study was students in East Java with a total sample of 125. The sampling technique used was accidental sampling and data analysis using SEM. The results of this study are: 1) there is an influence of the contextual factors on the interest in entrepreneurship. This is based on standardized output parameter coefficient of 0.524 with p= *** (significant at p = 0.001). 2) There is an influence of personality factors on the interest in entrepreneurship. This is indicated by the standardized output parameter coefficient of 0.472 which is significant at p = 0.001 (p = ***). The conclusion of this study is contextual factors and personality factors influence the interest in student entrepreneurship.Keywords: interest in entrepreneurship, contextual factors, personality factors, student’s entrepreneurship, improve student competency